An introduction to the special issue on the past, present and future research on deliberate lookalikes. Issue 6 (16th September 2019) - Davcik, Nebojsa S.; Sharma, Piyush; Chan, Ricky; Roy, Rajat
Abstract : Purpose: The purpose of this paper is to present the contemporary thinking on deliberate lookalikes and to provide a better understanding of its key forms (counterfeits, copycats and no-name imitations) and markets (deceptive and non-deceptive). Design/methodology/approach: This editorial contains a review of current and past literature on deliberate lookalikes along with summaries of all the articles accepted for publication in the special issue on deliberate lookalikes. The guest editors used academic databases such as Web of Science to find the most representative scholarly work on deliberate lookalikes literature. Findings: This editorial identifies pertinent research gaps in the literature on deliberate lookalikes. The five selected articles address some of these research gaps and provide useful insights on the purchase and usage of deliberate lookalikes along with directions for future research and ways to apply different research methods that could have important implications for scholars and managers. Originality/value: The editorial and special issue extends the knowledge about the deliberate lookalikes and their effects on firms, brands and consumers. This work opens new avenues for the research about different forms and markets in the context of lookalikes.